FIKIH DAN KESEHATAN (Tinjauan terhadap Hukum Terapi Urin) - Sulastri Caniago (Institut Agama Islam Negeri Batusangkar, 2018)
Urinal therapy is a popular alternative medical treatment recently. In Islam, urin is considered as najis (dirty matter) that block a Moslem to perform worship if it sticks to his/her body or to the clothes he/she is wearing and therefore he/she needs to purify him/herself. Islamic scholars (ulama) agree that urin belongs to dirty matter and consuming it is considered to commit to sinful deed. However, as a flexible religion, Islam tolerates forbidden deeds (haram) in true emergency situations, such consuming urin for medical purposes, if the only choice which is available.